Respostas
respondido por:
1
a)
![( \sqrt[3]{4} ) ^{2} = \sqrt[3]{ 4^{2} } = \sqrt[3]{16} = \sqrt[3]{ 2^{3} .2} =2 \sqrt[3]{2} ( \sqrt[3]{4} ) ^{2} = \sqrt[3]{ 4^{2} } = \sqrt[3]{16} = \sqrt[3]{ 2^{3} .2} =2 \sqrt[3]{2}](https://tex.z-dn.net/?f=%28+%5Csqrt%5B3%5D%7B4%7D+%29+%5E%7B2%7D+%3D+%5Csqrt%5B3%5D%7B+4%5E%7B2%7D+%7D+%3D+%5Csqrt%5B3%5D%7B16%7D+%3D+%5Csqrt%5B3%5D%7B+2%5E%7B3%7D+.2%7D+%3D2+%5Csqrt%5B3%5D%7B2%7D+)
b)
![( \sqrt{5} ) ^{2} = \sqrt{ 5^{2} } =5 ( \sqrt{5} ) ^{2} = \sqrt{ 5^{2} } =5](https://tex.z-dn.net/?f=%28+%5Csqrt%7B5%7D+%29+%5E%7B2%7D+%3D+%5Csqrt%7B+5%5E%7B2%7D+%7D+%3D5)
b)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás